Overexpression of GmBIN2, a soybean glycogen synthase kinase 3 gene, enhances tolerance to salt and drought in transgenic Arabidopsis and soybean hairy roots - Ling-shuang WANG; Qing-shan CHEN; Da-wei XIN; Zhao-ming QI; Chao ZHANG; Si-nan LI; Yang-mei JIN; Mo LI; Hong-yao MEI; An-yu SU; Xiao-xia WU (Journal of Integrative Agriculture, 2018)
Glycogen synthase kinase 3 (GSK3) is a kind of serine/threonine kinase widely found in eukaryotes. Many plant GSK3 kinases play important roles in regulating stress responses. This study investigated BRASSINOSTEROID-INSENSITIVE 2 (GmBIN2) gene, a member of the GSK3 protein kinase family in soybean and an orthologue of Arabidopsis BIN2/AtSK21. GmBIN2 expression was increased by salt and drought stresses, but was not significantly affected by the ABA treatment. To examine the function of GmBIN2, transgenic Arabidopsis and transgenic soybean hairy roots were generated. Overexpression of GmBIN2 in Arabidopsis resulted in increased germination rate and root length compared with wild-type plants under salt and mannitol treatments. Overexpression of GmBIN2 increased cellular Ca2+ content and reduced Na+ content, enhancing salt tolerance in transgenic Arabidopsis plants. In the soybean hairy root assay, overexpression of GmBIN2 in transgenic roots also showed significantly higher relative root growth rate than the control when subjected to salt and mannitol treatments. Measurement of physiological indicators, including proline content, superoxide dismutase (SOD) activity, and relative electrical conductivity, supported this conclusion. Furthermore, we also found that GmBIN2 could up-regulate the expression of some stress-related genes in transgenic Arabidopsis and soybean hairy roots. Overall, these results indicated that GmBIN2 improved tolerance to salt and drought in transgenic Arabidopsis and soybean hairy roots.